Diabetes Mellitus Associated with Sputum Conversion Time in Drug-Resistant Pulmonary TB Patients at Dr. Soebandi Regional General Hospital, Jember - Rahami, Nahla Ahmad; Dewi, Rosita; Raharjo, Angga Mardro; Abrori, Cholis; Hermansyah, Yuli; Shodikin, Muhammad Ali (Jurnal Respirasi, 2024)
Introduction: Diabetes mellitus (DM) comorbidity in drug-resistant (DR) pulmonary tuberculosis (TB) patients can be associated with the treatment outcome. In DR-TB patients with DM, the immune system is impaired, which will decrease the success of treatment. Sputum conversion time is an indicator used to predict the treatment outcome. However, there is still no further study related to the association between DM comorbidity and the sputum conversion time in DR-TB patients, especially in Jember. This study aimed to determine the association between DM and sputum conversion time in DR-TB patients at Dr. Soebandi Regional General Hospital, Jember. Methods: This was an analytic observational study with a cross-sectional design. A total of 122 samples of DR-TB patients were taken using the purposive sampling method in 2018-2023 at Dr. Soebandi Regional General Hospital, Jember. The data were analyzed using the Chi-square and logistic regression statistical test. Results: Chi-square analysis showed that DM (p = 0.015; OR = 2.604; 95% CI 1.195-5.674) and age (p = 0.021; OR = 0.377; 95% CI 0.162-0.878) were associated with sputum conversion time. Logistic regression showed that DM was the most associated variable with the sputum conversion time (p = 0.016; OR = 2.604; 95% CI 1.195-5.674) compared to gender, age, TB resistance type, and anti-TB regimen. Conclusion: DM is associated with prolonged sputum conversion time in DR-TB patients at Dr. Soebandi Regional General Hospital, Jember. DM was also the most associated variable with the sputum conversion time compared to gender, age, TB resistance type, and anti-TB regimen.